2014
DOI: 10.2478/s13545-014-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the accumulation of pentachlorophenol — a precursor of dioxins in bottom sediments of the Gulf of Gdańsk (Baltic Sea)

Abstract: Pentachlorophenol (PCP) and its derivatives are considered to be the precursors of dioxins, thus their concentrations in environmental compartments remain relatively correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, although PCP and Na‐PCP are thought not to be produced in the area of the Pilica River catchment, it does not mean that they were not used in the area. Lewandowski et al (2014) and Kobusińska et al (2014) noted contamination with PCP in the bottom sediment of the mouth section of the Vistula River (the Pilica River receiver) and the Gulf of Gdańsk. In addition, PCDD congeners are less water soluble than PCDFs, reflected in their octanol–water partition coefficient ( K OW ) (Shiu et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…However, although PCP and Na‐PCP are thought not to be produced in the area of the Pilica River catchment, it does not mean that they were not used in the area. Lewandowski et al (2014) and Kobusińska et al (2014) noted contamination with PCP in the bottom sediment of the mouth section of the Vistula River (the Pilica River receiver) and the Gulf of Gdańsk. In addition, PCDD congeners are less water soluble than PCDFs, reflected in their octanol–water partition coefficient ( K OW ) (Shiu et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…The sedimentary conditions in the presented regions are related mainly to mixing of riverine and marine water masses, and a significant content of organic matter in the transported material is known to be conducive to sedimentation via flocculation (Konat & Kowalewska 2001, Szymczak et al 2013. In this region, increased concentrations of other organic pollutants, such as pentachlorophenol, polychlorinated biphenyls or mercury, have been recorded (Konat & Kowalewska 2001, Szefer 2002, Kobusińska et al 2014. However, the offshore regions are more susceptible to contamination by the atmospheric deposition, which is the case of organic pollutants such as dioxins (Larsson et al 2000).…”
Section: Surface Sedimentsmentioning
confidence: 95%
“…e previous research revealed that the highest concentration of PCP wasobserved in the surface layer of bottom sediments from the Gdańsk Basin, suggesting a continuous in ow of this contaminant by the Vistula River and its sedimentation (Kobusińska et al 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Unlimited use of the PCP technical solvent, which contained about 14% of other, so-called microcontaminants, including polychlorinated dibenzo-p-dioxins and dibenzo-furans (PCDD/F), polychlorinated biphenyls (PCBs) and hexachlorobenzene (HCB), has resulted in an increased supply of PCP to agricultural lands, and hence its discharge into the Baltic Sea. Despite the restrictions on its use, high concentrations of this compound are continuously recorded in the marine environment (Kobusińska et al 2014;Lewandowski et al 2014).…”
Section: Introductionmentioning
confidence: 99%